Rankings Tax Affairs Office Of The East Of Tehran With The Tax Capacity Approach Using Topsis Method - Movahedy, Somayeh (The Turkish Online Journal of Design Art and Communication, 2016)
Taxation is the most important tool of the government's fiscal policy, which speeds up the process of economic growth, and constitutes one of the most major and most stable sources of income for governments. Comparison this source with other sources suggests that, whatever the contribution of taxes is more in provision of government expenditures, economic adverse effects are reduced, significantly. Accordingly, it is necessary to taxation problems, be analyzed by estimating the throughput and efficiency of the tax system, and practice, in order to overcome them, and to identify new ways of taxing, to reduce exist tax gap between tax revenues and tax capacity, by adopting the methods and measures. In the present study, as the regional study, is trying to rank Affairs tax Office of East of Tehran, by examining six factors influencing the actual capacity of tax, as amount of tax collecting, number of tax employees, etc, and testing their effectiveness with TOPSIS method, based on information from 2011, to evaluate the inter-organizational factors influence the capacity of the tax. In this study, researcher collected research data, without any kind of tampering, and with the help of interviews with tax experts, and visiting the tax affairs offices of East of the state. The results of the entropy technique, showed that the amount of collected taxes, with weight 0.2444, has the most importance, and the ratio of the number of records, compared with number of employees, with the weight of 0.0412, has the lowest importance among six identified indicators. Finally, it was determined that, among the tax Affairs Offices of East of Tehran, tax affairs office of Boomehen, with CA₂*=0.7099, is the first, and tax affairs office of Pardis, with the CA₁* =0.2493, is on the last place.
Keywords: Tax affairs office; tax actual capacity; weight indicators; entropy technique; TOPSIS Method